CHALLENGES OF SUSTAINABLE DEVELOPMENT GOALS "CLEAN WATER AND SANITATION": SCIENCE LEARNING INNOVATION THROUGH ANDROID-BASED LEARNING MEDIA AND WATER PURIFICATION PRACTICE WITH PROBLEM-BASED LEARNING MODELS - Arum, Vita Kartika; Tapilouw, Marisa Christina; Sucahyo, Sucahyo (JURNAL SPEKTRA, 2024)
Sustainable Development Goals (SDGs) is the United Nations’ effort so that by 2030 all people of the world can enjoy peace and prosperity. one of the SDGs goals is clean water and sanitation. This provides opportunities for science learning innovation. The development of IT can make learning interesting and positive academic performance. This provides an opportunity to develop Learning Media which is Android operating system. The objective of this study is to innovate learning through the development of learning media in Indonesian Ecology and Biodiversity material that is integrated with SDGs, and test its effectiveness. The study wad done in class VII at the even semester of the 2022/2023 by using Research and Development method with 4D (Define, Design, Develop, Dissemination). From the” Define” stage, science learning in the form of Android powerpoints and water purification practice was potential to develop. In the “Design” stage, learning media design using water biota’s theme and turquoise green’s background, black font, and font size that adjust with layout size.  In the “Develop” stage, the score of media feasibility was 8 (valid) and material feasibility was 8.56 (valid). The score of water purification device was 9.22 (valid). In the “Disseminate” stage, the achievement of knowledge is measured from the results of pre-test (58.8) and post-test (68.8). The N Gain score of the test was 0.23.  From the result, the score of Student Worksheets was 94.34 and practice was 78.03. Finally, the innovations through Android-based learning and water purification practice were effective (> 3.40).